Factors that Improve Performance with Competence as a Moderating Variable in Government Internal Supervisory Apparatus in Riau Island Province - Evi Silvana Muchsinati; Ernis Yunianti; Dessy Aliandrina (Dinasti International Journal of Education Management And Social Science, 2025)
The Government Internal Supervisory Apparatus (APIP) plays a vital role in supporting the success of regional development by ensuring that the implementation of the Regional Budget (APBD) is carried out effectively and efficiently. To fulfill this strategic role, APIP must demonstrate strong performance, which in turn must be supported by improvements in other key elements that influence performance. Through the competency of Inspectorate of Riau Islands Province personnel, this study seeks to assess the influence of work culture, work environment, and education and training on APIP performance. Utilizing a questionnaire instrument, a quantitative research technique was utilized. Data was gathered from 170 respondents selected by purposive sampling. Structural Equation Modeling (SEM) was used to assess the data. While the work environment did not demonstrate a substantial influence on APIP performance, the data suggest that work culture does. Performance was discovered to be positively affected by education and training. In addition, the correlation between competence and both work culture and performance and work environment and performance was demonstrated. There was a correlation